Sprachatlas des Dolomitenladinischen und angrenzender Gebiete Band 5 - Goebl, Hans (Editions de Linguistique et de Philologie, 2012)
The fifth volume contains 216 dialect maps which embrace dialectal terminologies from the chicken breeding to the verb stare ("to stay").